2021
DOI: 10.31261/tapsla.8431
|View full text |Cite
|
Sign up to set email alerts
|

Using Character Strengths to Address English Writing Anxiety

Abstract: Positive psychology has been introduced to the applied linguistics literature with the broad goal of improving the experience of language learners and teachers through a variety of interventions (MacIntyre & Mercer, 2014; Gabryś-Barker & Gałajda, 2016). “The aim of positive psychology is to catalyze a change in psychology from preoccupation only with repairing the worst things in life to also building the best qualities in life” (Seligman &Csikszentmihalyi, 2000, p. 5). One significant contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Follow-up experimental or complexity-based research should be conducted to investigate this further, however. Gregersen et al (2021) point out the need to examine the fit between the individual and the PP activity being used (p. 11). The individualized nature of the intervention meant that the learners could choose tactics that they had self-rated themselves lowly on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up experimental or complexity-based research should be conducted to investigate this further, however. Gregersen et al (2021) point out the need to examine the fit between the individual and the PP activity being used (p. 11). The individualized nature of the intervention meant that the learners could choose tactics that they had self-rated themselves lowly on.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for more intervention studies that demonstrate how teachers can help learners to maximize their well-being and their learning (MacIntyre et al, 2019;Mercer, 2021). Further, research has shown such interventions may be most effective when they are individualized (Gregersen et al, 2016;Gregersen et al, 2021), with Gregersen et al (2021) stating that "we need to examine in detail the fit between the individual and the PP activity, and document the process by which it exerts its effect" (p. 11). Rebecca Oxford has proposed the EMPATHICS theoretical framework (Oxford, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using Signature Strengths and EAL writers EAL writers are also vulnerable as they experience the disruptive and unwelcome negative effects of anxiety arousal. Similar to the above research using the AI approach, Gregersen et al (2021) conducted a mixed-methods case study to explore whether an individual EAL writer using their signature strengths in novel ways could set anxiety aside to work on interventions that psychologically build up their strengths. Several reasons supported our use of an N-of-1 study.…”
Section: Appreciative Inquiry and Preservice Language Teachersmentioning
confidence: 99%
“…In continuation, I briefly describe two studies the results of which both support the implementation of PP in combatting anxiety; in particular, a focus on the positive through the feedback process of appreciative inquiry in preservice language teachers (Gregersen & Mercer, 2022; Gregersen et al, 2022) and the recognition and utilization of one's signature strengths in learners of English as an additional language (EALs) (Gregersen et al, 2021).…”
mentioning
confidence: 99%